2017
DOI: 10.1080/20786190.2017.1292693
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and determinants of fertility levels among women of childbearing age in Nigeria

Abstract: Background: Despite aggressive measures to control the population in Nigeria, the population of Nigeria still remains worrisome. Increased birth rates have significantly contributed to Nigeria being referred to as the most populous country in Africa. This study analyses spatial patterns and contributory factors to fertility levels in different states in Nigeria. Method: The 2013 Nigerian Demographic Health Survey (NDHS) data were used to investigate the determinants of fertility levels in Nigeria using the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 20 publications
(25 reference statements)
20
26
1
Order By: Relevance
“…This study showed that the number of children from poor households was higher than children from rich households, and this is in agreement with other studies [11,15,25]. This may indicate that parents in poor households use children as a source of income.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that the number of children from poor households was higher than children from rich households, and this is in agreement with other studies [11,15,25]. This may indicate that parents in poor households use children as a source of income.…”
Section: Discussionsupporting
confidence: 93%
“…According to the result, parental education level is an important socio-economic predictor of fertility, that is, fertility rate decreases with increase in parental education level. This result in lined with the previous study, the higher level of maternal and husbands education, the lower fertility [11,12,14,16,22,24,25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fertility behavior has been found to have a spatial dimension and varies among places and between urban and rural areas across the world (Kulu and Boyle, 2009;Kulu, 2013;Fiori et al, 2014;Odimegwu and Adedini, 2017;Jung et al, 2019). The situation is not different in Nigeria where it has further been shown to vary among different ethnic groups (Odimegwu, 1999;Ushie et al, 2011;Mberu and Reed, 2014;Odimegwu et al, 2014;Alaba et al, 2017;Adebowale, 2019). For instance, when expressed in terms of total fertility rates (TFR), the fertility pattern in rural Nigeria is 5.9 births while it is 4.5 in the urban centers (National Population Commission (NPC) [Nigeria] and ICF, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Alaba, Olubusoye and Olaomi [2] used the geoaditive Bayesian model based on Negative Binomial distribution as a measure of overdispersion to investigate the spatial determinants of fertility differentials in Nigeria. Majumder and Ram [23] investigated the role of proximate determinants on fertility decline among poor and non-poor in Asian countries.…”
Section: Introductionmentioning
confidence: 99%